HUBUNGAN PENGETAHUAN GIZI DENGAN PEMILIHAN MENU MAHASISWI UNIVERSITAS SARJANAWIYATA TAMANSISWA DI ASRAMA ASMADEWA YOGYAKARTA - Laily Miftahul Jannah (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2016)
This study aimed to describe (1) the nutrient knowledge, (2) the choice of menu, and (3)correlation between nutrient knowledge withthe choice of menu among the students of Sarjanawiyata Tamansiswa University in Asmadewa Hostel of Yogyakarta. This study was expost facto. Data colleting methods used questionnaires and documentation. Data analyzingmethods used descriptive analysis and hypothesis testing by using Product Moment that wasstarted by normality and linearity test. Thisstudy shows that the nutrient knowledge was inhigh category with the relative frequency 70.5%and the choice of menu was in high categorywith relative frequency 70.49%. Based on theresult of Product Moment, the score of rxy was0,642. The score of r table in the significantlevel 5% for total respondents 135 was 0.254((rxy 0,642 > r table 0,254). It could be statedthere was a positive and significant correlationbetween nutrient knowledge with the choice ofmenu. The determinant coefficient (R2) was0.416, it means that nutrient knowledge gavecontribution for about 41.6% toward the choiceof menu, while 58.4% was influenced by otherfactors that were not discussed in this study;such as location of the restorant, willing, andeconomic level.